Peran Pendidikan dalam Meningkatkan Mobilitas Sosial di Era Modern - Hifni Laila Nashifah; Nur Khasanah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Education plays a strategic role as an agent of social mobility in modern society. From an Indonesian sociological perspective, education serves as the primary means of transmitting the values, skills, and competencies needed in an increasingly complex social structure, as argued by Soerjono Soekanto. By expanding access to education, improving the quality of learning, and adapting the curriculum to the demands of the job market, education can open up opportunities for individuals to improve their socioeconomic status. Indonesian educational literature, emphasizes that educational institutions not only shape character but also serve as a meritocratic mechanism that enables vertical social mobility. However, the challenges of the modern era including unequal access, the digital divide, and the mismatch between graduate competencies and industry needs still limit the optimization of education as a driver of social mobility. Therefore, comprehensive educational reform is needed through equalizing quality, strengthening technological innovation, and collaboration between the government, educational institutions, and the industrial world. With these steps, education can play a more effective role in realizing a more equitable social structure and more inclusive social mobility.